Finite size effect on dissociation and diffusion of chiral partners in Nambu-Jona-Lasinio model *PD thanks to Women Scientist Scheme A (WOS-A) of the Department of Science and Technology (DST) funding with (SR/WOS-A/PM-10/2019). (1st April 2022) - Deb, Paramita; Ghosh, Sabyasachi; Prakash, Jai; Das, Santosh Kumar; Varma, Raghava
Abstract: The masses of pion and sigma meson modes, along with their dissociation in the quark medium, provide detailed spectral structures of the chiral partners. Collectivity has been observed in pA and pp systems both at LHC and RHIC. In this research, we studied the restoration of chiral symmetry by investigating the finite size effect on the detailed structure of chiral partners in the framework of the Nambu-Jona-Lasinio model. Their diffusion and conduction have been studied using this dissociation mechanism. It is determined that the masses, widths, diffusion coefficients, and conductivities of chiral partners merge at different temperatures in the restoration phase of chiral symmetry. However, merging points are shifted to lower temperatures when finite size effect is introduced into the picture. The strengths of diffusions and conductions are also reduced once the finite size is introduced in the calculations.